A Case study on dialogue translation in Indonesian version pride and prejudice: From perspective of conversational implicature - LIWENLIN (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: This paper seeks to address the literature gap by investigating how Pride and Prejudice translators dealt with issues of conversational implicature in the novel’s dialogue.Method: Conversations selected from Pride and Prejudice chapter 10 served as the data source. The sample size was 53 different quotes. We applied cooperative principles to the study of those statements. The research methods used in this paper combine a focus group discussion (FGD) and a comparative analysis (CA).Findings: Thirty statements were found to violate cooperative principle maxims. Modulation translation was primarily used to render this speech sounds into another language. In addition to the modulation translation method, standard equivalent, amplification, reduction, and transposition translation approaches were also utilised.Implications/Novel Contribution: If translators use this case study as a guide, they will better understand which translation strategies to employ. The case study could also be investigated from a sociolinguistic or second-language learning perspective.